Corpora for computational linguistics - Constantin Orasan; Le An Ha; Richard Evans; Laura Hasler; Ruslan Mitkov (Ilha do Desterro)
Since the mid 90s corpora has become very important for computational linguistics. This paper offers a survey of how they are currently used in different fields of the discipline, with particular emphasis on anaphora and coreference resolution, automatic summarisation and term extraction. Their influence on other fields is also briefly discussed.